Efek Penambahan Fraksi Semi Polar (F15-F19) Ekstrak Metanol Tapak Liman Pada Daya Hambat Amoksisilin dan Kloramfenikol Terhadap Bakteri Staphylococcus aureus dan Escherichia coli - Nurma Alifia Rakhma; Zainul Fadli; Rio Risandiansyah (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2020)
Introduction: Elephantopus scabr linn contains various compounds which have antibacterial activity. The addition of antibiotic with herbs may increase antibiotic activity. However previous studies on Elephantopus scabr linn was in the form of crude extract. Therefore, this study separates compounds these into Semi polar fraction to determine the antibiotic activity and what compounds were contained therein.Methods: Methanol extract was fractionated using silica gel stationary phase and mobile phase 75 ml of ethyl acetate: 25 ml of methanol. Phytochemical test were carried out with dragendorff spray, FeCl3 and Formaldehyde on Thin layer Chromatography. The interaction between herbs and antibiotics was assessed based on the AZDAST method and the inhibitory assessment using the Kirby bauer method.Result: Five fractions (f15-f19) were obtained using fractionation. Fraction 15 contain alkaloids, and fraction 16-19 contains alkaloids and phenol. On a single test, fraction 16 had clear zones against S.aureus with a value 6,66 ± 0,57 mm. In the combination test, fraction 18 and 19 had an antagonistic interaction with amoxicillin in S.aureus. Combination of fractions 16-19 had antagonistic interaction with chloramphenicol in S.aureus.Conclusion: Fraction 16 of Elephantopus Scabr Linn metanolic extract was sinergistic with amoxicillin against S.aureus.Keywords: Semi Polar Fraction, Elephantopus scabr linn, S. aureus, E.coli